Peripheral Neuropathy in Children and Adolescents with Insulin-dependent Diabetes Mellitus - Ghaemi, Nosrat; Hasan Abadi, Hossein; Ashrafzadeh, Farah; Sarvari, Somaye; Rahimi, Hamidreza; Hashemian, Somayyeh (Iranian Journal of Child Neurology, 2018)
Introduction: Type 1 diabetes mellitus(T1DM) is a chronic immune-mediated disease. Diabetic peripheral neuropathy (DPN) is an important micro vascular complication of T1DM. One of the most important risk factors for the development of DPN is poor glycemic control. The aim of this study was to evaluate the prevalence of DPN among T1DM patients and to determine the association between DPN and glycated hemoglobin(HbA1c) level. Methods: The subjects were recruited prospectively upon initial evaluation at a tertiary hospital. Patients with T1DM were selected based on the inclusion criteria (i.e., age of 6≤years and absence of other co-morbidities). DPN was assessed through electro diagnostic studies and neurological examinations, while diabetes control was evaluated by measuring the HbA1c level. Results: In total, 50 patients with T1DM were enrolled in this study. The mean diabetes duration of patients was 8.38±3.79 years (mean age16.68±6.68 years). The mean HbA1c level was 8.6±2.1% in patients without DPN and 10.5±3 in those with DPN (P=0.016). Overall, 24% of the subjects were presented with DPN according to nerve conduction velocity(NCV) findings. A positive correlation was found between NCV and clinical symptoms with signs (P<0.001, r=0.45 and P<0.001, r=0.644, respectively). Sensitivity and specificity of neurological examination for DPN diagnosis were 91.7% and 63.2%, respectively. Our findings revealed that, poor diabetes control is associated with DPN. Also, HbA1c level was used as an index for glycemic control over the past six months. Conclusion: It seems that rigid blood glucose control and periodic neurological examinations were the best strategies to prevent DPN. Introduction: Type 1 diabetes mellitus(T1DM) is a chronic immune-mediated disease. Diabetic peripheral neuropathy (DPN) is an important micro vascular complication of T1DM. One of the most important risk factors for the development of DPN is poor glycemic control. The aim of this study was to evaluate the prevalence of DPN among T1DM patients and to determine the association between DPN and glycated hemoglobin(HbA1c) level. Methods: The subjects were recruited prospectively upon initial evaluation at a tertiary hospital. Patients with T1DM were selected based on the inclusion criteria (i.e., age of 6≤years and absence of other co-morbidities). DPN was assessed through electro diagnostic studies and neurological examinations, while diabetes control was evaluated by measuring the HbA1c level. Results: In total, 50 patients with T1DM were enrolled in this study. The mean diabetes duration of patients was 8.38±3.79 years (mean age16.68±6.68 years). The mean HbA1c level was 8.6±2.1% in patients without DPN and 10.5±3 in those with DPN (P=0.016). Overall, 24% of the subjects were presented with DPN according to nerve conduction velocity(NCV) findings. A positive correlation was found between NCV and clinical symptoms with signs (P<0.001, r=0.45 and P<0.001, r=0.644, respectively). Sensitivity and specificity of neurological examination for DPN diagnosis were 91.7% and 63.2%, respectively. Our findings revealed that, poor diabetes control is associated with DPN. Also, HbA1c level was used as an index for glycemic control over the past six months. Conclusion: It seems that rigid blood glucose control and periodic neurological examinations were the best strategies to prevent DPN.